Efektivitas Pemidanaan Non-Penjara dalam Mengurangi Overcrowding Lapas di Indonesia - Abdullah, Ahmad Danial; Faturrahman, M. Zaidan; Ul Hosnah, Asmak (Legalita, 2025)
The Indonesian correctional system is currently facing a severe overcrowding crisis, with occupancy rates exceeding 188% of its ideal capacity. The reliance on imprisonment as the primary form of punishment has led to an excessive number of inmates and reduced the effectiveness of rehabilitation programs. This study aims to analyze the effectiveness of non-custodial sentencing in reducing overcrowding in Indonesian correctional facilities, based on the theoretical assumption that alternative sanctions such as community service, supervision, and fines align more closely with restorative justice principles and the rehabilitative goals of modern criminal law. The research employs a normative juridical method supported by empirical data, focusing on legal instruments such as Law No. 1 of 2023 on the New Criminal Code and official data from the Directorate General of Corrections. The findings indicate that while non-custodial sentencing has significant potential to reduce overcrowding, its implementation remains constrained by the lack of technical regulations, institutional readiness, and the prevailing legal culture that continues to prioritize imprisonment. Consequently, the effectiveness of non-custodial sentencing in addressing prison overcrowding depends heavily on strengthening legal frameworks, enhancing institutional capacity, and promoting a paradigm shift toward a more humane and effective criminal justice system.